2009
DOI: 10.1002/cbic.200800822
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Indanomycin Biosynthetic Gene Cluster from Streptomyces antibioticus NRRL 8167

Abstract: Metabolites that harbor a core indane scaffold are found to have diverse biological properties. Indanomycin and related pyrroloketoindanes are ionophores and have demonstrated antiparasitic, insecticidal, and antibacterial activities. To understand the biochemical mechanisms guiding formation of the central indane ring, the biosynthetic gene cluster for indanomycin was identified from Streptomyces antibioticus NRRL 8167 and sequenced to approximately 80 kb; this revealed five genes encoding subunits of a polyk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 70 publications
0
63
0
1
Order By: Relevance
“…CYC11 is thought to catalyze the formation of the tetrahydropyran portion in 66. Two mechanisms for this reaction sequence have been postulated [175]. In one scenario, the precursor molecule gets dehydrated, either by action of CYC11 or by one of the preceding DH domains acting in trans, followed by a Michael addition to give the cyclic ether.…”
Section: Pyran Formation By Cyclase Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYC11 is thought to catalyze the formation of the tetrahydropyran portion in 66. Two mechanisms for this reaction sequence have been postulated [175]. In one scenario, the precursor molecule gets dehydrated, either by action of CYC11 or by one of the preceding DH domains acting in trans, followed by a Michael addition to give the cyclic ether.…”
Section: Pyran Formation By Cyclase Domainsmentioning
confidence: 99%
“…These experiments clearly showed 66 to be composed of an L-proline derived pyrrole moiety as well as six malonyl-CoA, two methylmalonyl-CoA, and an ethylmalonyl-CoA building block, thus evidencing the apparently The Catalytic Diversity of Multimodular Polyketide Synthases mixed NRPS-PKS pathway leading to this compound. Based on this information the Kelly lab succeeded in identification of the biosynthetic gene cluster encoding for 66 [175]. Bioinformatic analysis of this data revealed the presence of five modular type I PKSs (IdmL-P) harboring ten modules for the biosynthesis of the expected linear indanomycin precursor molecule with almost perfect compliance to colinearity rules (except for module 2, where the presence of a DH domain resulting in a C19-C20 double-bond might be required for the postulated formation of the indane portion of 66 by [4þ2] cycloaddition).…”
Section: Pyran Formation By Cyclase Domainsmentioning
confidence: 99%
“…It was thus postulated that IdmB accepted substrates such as acetyl-CoA, propionyl-CoA, and butyryl-CoA with almost equal affinities, just like acetylCoA carboxylases. [37,38] For the precursor supply in tiacumicin B biosynthesis, three genes encoding for enzymes of the ethylmalonyl-CoA pathway-a hydroxybutyryl-CoA dehydrogenase (TiaJ), a crotonyl-CoA hydratase (TiaN), and a crotonyl-CoA carboxylase (TiaK)-were identified. In addition to these three enzymes that form ethylmalonyl-CoA, another enzyme, a PCC encoded by tiaL, is believed to supply the PKS with methylmalonyl-CoA.…”
Section: Domains Encoded On Phn2mentioning
confidence: 99%
“…Li et al discussed the formation of an active complex with partnering BC and BCCP, encoded elsewhere within the genome of the strain in question. [38] The active site residue of Phn1 is an alanine unit, rather than the conserved aspartate residue found in PCCs ( Figure S2). Mutational experiments for a PCC in S. coelicolor showed that mutations of this type led to a clear shift in substrate preference [37,40] Phn1 is thus more likely a butyryl-CoA carboxylase (BCC) than a PCC, and hence preferentially provides ethylmalonyl-CoA for the PKS assembly line.…”
Section: Domains Encoded On Phn2mentioning
confidence: 99%
“…Sequence comparisons reveal no clear differences between AmbDH3 and monofunctional DH domains from either cis ‐ or trans ‐AT PKSs, so the basis of the dual activity is unknown. The cis ‐AT PKS for indanomycin (Figure 1) contains an integral domain (Cyc11) which has been proposed8h from gene cluster analysis to form the pyran at the western end of the molecule. However, experimental evidence for this is lacking.…”
mentioning
confidence: 99%